Boosting the Immunoactivity of T Cells by Resonant Thermal Radiation from Electric Graphene Films for Improved Cancer Immunotherapy. Issue 2 (10th November 2022) - Shi, Changrong; Fu, Wenxing; Zhang, Xinyi; Zhang, Qianyu; Zeng, Fantian; Nijiati, Sureya; Du, Chao; Liu, Xiaomin; Wang, Mingkun; Yao, Youliang; Huang, Hongling; Zheng, Nanfeng; et al.
Abstract: To investigate the effect of resonant thermal radiation from electric graphene films (GFs) to the immunoactivity of T cells in situ and the benefits to cancer immunotherapy. This work utilizes externally applied GFs to regulate the immunoactivity of T cells through the eminent resonant thermal radiation effect. The GFs are fabricated with high emissivity and well‐matched far‐infrared emission peaks between the GFs and living bodies. The T‐cell antigen receptor signaling mechanisms and the ensuing immunoactivity of T cells by GFs treatment, compared with traditional metal films (MFs), are studied both in vitro and in vivo. The resonance thermal radiation decreases the activation threshold of T cells by increasing the influx of calcium ions, neutralizing the negative charge of intracellular membranes and triggering the phospho‐CD3ζ event. As a result, GF treatment elicits an enhanced T‐cell‐based immune response and serves as an externally applied "adjuvant" to T‐cell activation, which shows remarkable efficiency in combination with aPD‐L1 immunotherapy in multiple mouse models. This work centers the unmet needs of regulating the immunoactivity of intratumoral T cells in situ, in which the auxiliary use of GFs with high efficiency and little safety concern has great promise to translational study regarding cancer immunotherapy in future. Abstract : This study reports the use of externally applied graphene films (GFs) to regulate the immunoactivity of T cells in situ through the eminent resonant thermal radiation effect, presenting an auxiliary means to sensitize tumors for improved anti‐PD‐L1 immunotherapy. The GFs with high efficiency and low systemic safety concern holds great promise to translational study regarding cancer immunotherapy.